Lectin Pathway Components And Its Transfer From Blood To Cerebrospinal Fluid - Ramos-Robledo, Alejandro; Meijides Mejías, Christian; Rodríguez Pérez, José Alejandro; Mirabal Viel, Alejandro; Pérez del Vallín, Vanessa; Dorta Contreras, Alberto Juan (Revista Cubana de Investigaciones Biomédicas, 2019)
Introduction: Defining mechanisms governing the diffusion from blood to cerebrospinal fluid is central to understanding immune function in the central nervous system. OBJECTIVE. To describe the dynamics of diffusion of the lectin pathway components from blood to cerebrospinal fluid. Methods: It was organized the information available in PubMed database and of papers from journals, and abstract books from international congresses belongs mainly to Cuban authors all about the lectin pathway of complement including manan-binding lectin (MBL) and ficolins complexed with the MBL-associated serine proteases (MASP2), and of other components like MASP3, Map44 as regulatory components and the different starters like MBL, ficolins and CLLK. Results: All the lectin pathways component are blood derived proteins but at the same time it could be synthesized intrathecally. Most of the protein can be transferred from blood to cerebrospinal fluid in different aggregation forms and some of them can be described as a consuming curve. The control mechanism of regulation the lectin pathway can be followed by molecules as MASP3 and Map44. Conclusions:The under- constructed lectin pathway of the complement system required not only the available information in different journals. It had to be completed by reviewing the congress abstract book and congress website of the last years